Performance and Explainability of Machine Learning Models in Phishing Detection Using SHAP - Gharkan, Dhurgham Kareem (Al-Mustansiriyah Journal of Science, 2025)
Background: Phishing is a common cybercrime attack, and it is also considered a social crime that has been going on for more than two decades. Phishing aims to trick users into revealing their private information, including banking information, passwords, and account credentials. Phishing remains a real threat and usually occurs via instant messages, email, or phone calls. Objective: Used shape analysis on the system to uncover the most important features that contribute to phishing detection. A set of key features was identified. Many phishing detection methods have been used recently, but they do not provide a complete understanding of the impact of different features on predictions. Methods: Several machine learning strategies based on SHAP (Shappley Additive Explanations) were applied, which enhanced the classification model. This paper proposes a fast model based on a set of contemporary machine learning techniques. Results: Experiments showed that the proposed model achieved a maximum accuracy of 99.1% for K-NN and 98.5% for XGBoost on the Phishing_Legitimate_full dataset. K-NN has demonstrated superior performance and interpretability, which is critical for security-critical applications. Conclusions: The results highlight the balance between predictive performance and interpretability. This provides valuable transparency into the decision-making process. This makes it a more practical choice for real-world phishing detection systems, where reliability and interpretability are critical.